Floristic diversity in calamine areas of the Silesia-Cracow Monocline - Jędrzejczyk-Korycińska, Monika (Biodiversity: Research and Conservation, 2006)
The study presents results of floristic investigations conducted in areas with high concentration of heavy metals in the substrate, where zinc and lead ore deposits have been mined for many ages. Five sites were selected for a detailed investigation, located in three regions of the Silesia-Cracow Monocline. In the course of field studies, 362 vascular plant species, belonging to 73 families and 232 genera, were recorded. A group of 44 species was common for all investigated sites. Based on the analysis of vascular flora diversity in the areas under the study, it was determined that the majority of species are native hemicryptophytes. The largest proportion are thermophilic and heliophilic species of meadows and grasslands, while a large part of the flora is formed by species connected with moderately poor and mineral, and humus-rich types of soil. A noteworthy fact is the occurrence of numerous plants connected with moist and humid soils, despite the unfavorable humidity conditions. The share of halophytes and species with increased heavy metal tolerance is also conspicuous. The flora of majority of investigated abandoned mining sites includes common species characterised by extensive plasticity and numerous adaptations to the habitat conditions present in the study areas, as well as a range of species which belong to the group of protected, rare or threatened plants.